An Analysis of Real effective Exchange Rates on Trade Balance in Pakistan: 1980-2008 - Asif, Mahamaad (Economic Journal of Nepal, 2014)
The purpose of this paper is to find whether the devaluation using REER is effective in improving the trade balance in Pakistan or not. The bound testing approach of ARDL is used to estimate the long run relationship among the variables, after getting stationarity through ADF test. The time series annual data from 1981 to 2008 were used to estimate the results. The result shows that a 1 percent increase in trade balance will result in about 0.066, 0.191 and 0.280 percent decrease in GDP, REER and WR respectively. There is a long run relationship amongst the variables as F-statistic value is higher than the upper bound critical values at the 1 percent level of Pesaran. The currency devaluation is not only mean to correct the trade balance deficit but also use other measures like direct control, tariff and quotas to improve the export and discourage the imports. The Economic Journal of Nepal, Vol. 34, No. 3, July-September 2011